2001
DOI: 10.1103/physrevlett.86.4029
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-Pasta-UlamβModel: Boundary Jumps, Fourier's Law, and Scaling

Abstract: We examine the interplay of surface and volume effects in systems undergoing heat flow. In particular, we compute the thermal conductivity in the Fermi-Pasta-Ulam beta model as a function of temperature and lattice size, and scaling arguments are used to provide analytic guidance. From this we show that boundary temperature jumps can be quantitatively understood, and that they play an important role in determining the dynamics of the system, relating soliton dynamics, kinetic theory, and Fourier transport.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
115
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 24 publications
(33 reference statements)
16
115
1
Order By: Relevance
“…It is now well established by computer simulations that the heat conductivity in FPU lattices diverges when the size of the lattice goes to infinity [8,9,10,11,12]. The simulations give a power law dependence of the heat conductivity on the number of particles N as approximately N 2/5 .…”
Section: Introductionmentioning
confidence: 94%
“…It is now well established by computer simulations that the heat conductivity in FPU lattices diverges when the size of the lattice goes to infinity [8,9,10,11,12]. The simulations give a power law dependence of the heat conductivity on the number of particles N as approximately N 2/5 .…”
Section: Introductionmentioning
confidence: 94%
“…This was done largely to examine how small the higher order terms (e.g., cubic, quartic) must be in order to preserve the phenomenon. In addition, the many questions it spawned have been the subject of experts in non-linear dynamics for decades and tremendous progress has been made [15][16][17] . Excellent reviews of that progress are available elsewhere 14,[18][19][20] and one of the prevailing theories for understanding the origin of the phenomenon is that of mode-coupling theory, which was pioneered by Lepri, Livi, and Politi 19 , and the notion that the reduced dimensionality is the origin of the anomalous thermal transport 19 .…”
mentioning
confidence: 99%
“…Finally, we want to discuss the role of the boundary resistance in connection with the temperature dependence of conductivity. In fact, an interesting application of (2.128) has been proposed with reference to the FPU-β model [155]. There, it has been empirically found that the bulk conductivity scales with N and T as…”
Section: Numerical Studies Of the Divergence Of Heat Conductivitymentioning
confidence: 99%